Risk assessment for transformer loading. - Weihui Fu (IEEE Transactions on power systems)
A risk-based probabilistic method is presented to assess transformer loading capability, taking into account the probabilistic nature of time-varying loads and ambient temperature. A sample calculation, with both component level analysis and system level analysis, is given. Quantitative reference risk levels are obtained based on reference loading levels given by IEEE/ANSI C57.115-1991. It shows that our quantitative risk assessment is useful in assessing transformer loading and in aiding related decision making. An additional benefit is that it enables inclusion of transformer loading in composite system risk analysis